Innovation Unleashed: Empowering Autistic Learners with Revolutionary Strategies and Technology - Moses Adeleke Adeoye; Hammed Olalekan Bolaji; Ajoke Kudirat Yahaya; Justina Ojoma Attah (Jurnal Pedagogi dan Pembelajaran, 2023)
An explosion of innovation using intelligence and software can potentially revolutionize growth strategies. Exploring new strategies to empower autistic students is crucial because they often experience difficulties in conventional educational environments. Based on this, this research aims to analyze the empowerment of autistic students and the use of the latest techniques and technology. This type of research is qualitative research. The method used in this research is a literature study. The method used to collect data is documentation. The instrument used to collect data was a questionnaire. The technique used to analyze data is qualitative descriptive analysis. The research results show that providing appropriate support and inclusive educational opportunities for autistic students is the most important thing. By offering tailored support, autistic students can develop essential skills for navigating various aspects of life. For example, helping them improve their social communication skills can improve their ability to form meaningful relationships and engage in collaborative activities. The need for personalized teaching and support is emphasized throughout the article as a means of addressing the unique demands of autistic students. Technology can help autistic people communicate, develop social skills, and become more independent. It is concluded that the transformative role that innovation plays in empowering autistic students and supporting the creation and adoption of innovative teaching methods and technologies on an ongoing basis.